Survey of knowledge, attitudes and practice regarding adverse drug reaction (ADR) reporting among community pharmacists in Selangor, Malaysia - Zin, Rosdi Md; Hong, Yet Hoi; Ming, Long Chiau; Khan, Tahir Mehmood; Dali, Ahmad Fauzi; Neoh, Chin Fen (Wiley, 2019)
Background: Community pharmacists play a pivotal role in adverse drug reaction (ADR) reporting because they provide services to a large proportion of the community. Although ADR reporting by healthcare providers in Malaysia is increasing, few ADR reports are submitted by community pharmacists. Aim: This study assessed the knowledge, attitudes and practice of ADR reporting, as well as barriers and facilitators of ADR reporting, among community pharmacists in Malaysia. Methods: A cross-sectional 52-item validated questionnaire was distributed to 278 community pharmacists in Selangor, Malaysia, in 2015. Multistage sampling was performed whereby community pharmacists from three of the nine administrative districts in the region were eligible for inclusion. Community pharmacies were then randomly sampled from the selected districts. Data are reported using descriptive statistics. Results: A total of 219 pharmacists responded to the survey, giving a response rate of 78.8%. These community pharmacists self-reported a positive attitude towards ADR reporting. Nevertheless, less than half (34.2%; n = 75) had previously reported an ADR. Lack of information provided by the patient, insufficient clinical knowledge and uncertainty relating to the association between the adverse reaction and the drug were the main barriers to ADR reporting. Conclusions: The attitude and practices among community pharmacists indicates there is room for improvement in ADR reporting in Malaysia. Ongoing education and training on ADR reporting for community pharmacists is required to ensure delivery of high-quality care to the community.